ANALYSIS OF ONLINE LEARNING SERVICES’ STUDENT SATISFACTION USING THE IMPORTANCE-PERFORMANCE ANALYSIS APPROACH - Sutiman, Sutiman; Pamungkasari, Eti Poncorini; Suprapti, Suprapti (Universitas Gadjah Mada, 2023)
Background: The education sector is adapting in order to suppress the spread of the Corona Virus-19 through distance learning policies. Universities are required to continue to carry out teaching and learning activities using online learning method, including medical education. Medical education has the characteristics of problem-based learning, which consists of theoretical lectures, tutorials, laboratory sessions, and skills labs for clinical skills. The implementation of online lectures needs to be evaluated with measurable instruments to identify obstacles and determine the direction of improvement. The study aims to determine the gap in the quality of online lecture services and the direction of service improvement using the importance-performance analysis method.Methods: This study was conducted by the survey method using a quantitative approach. Questionnaires were distributed to 250 students from 684 populations in the Sebelas Maret University medical study program. The results of the study were analyzed using Importance-Performance Analysis.Results: Out of the 24 attributes, the IPA analysis showed five aspects need to be improved. Attributes in quadrant I as main priorities are responsiveness of lecturers, responsiveness of education staff, technical assistance in online learning constraints, suitability of materials, access to contact lecturers, and communication between lecturers and students.Conclusion: According to the results of the importance-performance analysis method approach, student satisfaction will be achieved by improving services that are in quadrant I, which is the implementation of online learning.